PENYERAPAN TENAGA KERJA DI WILAYAH DKI JAKARTA PADA TAHUN 1990-2019 - Febrianty, Monica; Juliannisa, Indri Arrafi (2021)
Labor absorption in DKI Jakarta, if measured through the employment rate, already has a fairly good ratio where the growth rate has exceeded 90% in the last 5 years, but that is still a challenge due to the low quality when viewed from the existing education level. The level of investment has not optimally absorbed labor because it focuses on capital-intensive rather than labor-intensive. As well as wages that are increasing every year should have a positive impact but can be considered a burden by the company. The type of data used is secondary data with multiple linear regression models. The results obtained are that the Education Level of the Workforce and the Provincial Minimum Wage have an effect, while foreign investment and domestic investment have no effect on labor absorption in the DKI Jakarta area. Suggestions for future researchers are expected to look for other variables that affect labor absorption so that the research results can be more developed and more useful and add other research objects. For the government, it is expected to provide policies to address education, investment both foreign and domestic investment as well as the provincial minimum wage.